Ready-to-eat cereal is an affordable breakfast option associated with better nutrient intake and diet quality in the US population - Zhu, Yong; Jain, Neha; Normington, James; Holschuh, Norton; Sanders, Lisa M. (Frontiers in Nutrition, 2023)
Background: Results from observational studies have reported ready-to-eat cereal (RTEC) consumers have higher dietary quality and nutrient intake compared to consumers of non-RTEC breakfasts or those who do not eat breakfast. Yet, there have been few investigations on the relationship of RTEC to meal costs at breakfast and across the day, which may be one reason some consumers choose to not consume breakfast. Objective: The objective of this study is to evaluate the contribution of RTEC consumed at breakfast to nutrient intake and adequacy, diet quality and meal costs in a nationally representative sample of children and adults in the US. Methods: Dietary data from 2259 children (2-18 years) and 4776 adults (≥19 years) in the National Health and Nutrition Examination Survey (NHANES) 2017 – 2018 were evaluated to compare nutrient intake, adequacy, dietary quality, and food costs in RTEC breakfast consumers, non-RTEC breakfast consumers and those who did not consume breakfast. Results: RTEC breakfast consumers made up 28% of children and 12% of adults. Children and adults consuming RTEC for breakfast had higher intakes of carbohydrate, dietary fiber, calcium, magnesium, iron, zinc, phosphorus, potassium, B vitamins, vitamins A and D, whole grains, and total dairy compared to consumers of non-RTEC breakfast or no breakfast. There were no differences by breakfast status for sodium, saturated fat, or added sugar, except adults consuming RTEC had lower added sugar intake compared to those who did not consume breakfast. RTEC breakfast consumers were also more likely to meet estimated average requirements (EAR) for intake of several nutrients and had overall higher dietary quality. For children, breakfast meal costs were less for RTEC breakfast compared to non-RTEC breakfast, but total daily meal costs were similar for consumers of RTEC and non-RTEC breakfasts. Conclusion: RTEC breakfasts may contribute to greater nutrient intake and diet quality in children and adults in the US without increasing total daily meal costs.